Structural-phase state and properties of sprayed plasma coatings based on self-fluxing alloy of NiCrBSi system with the addition of shs composites - Sytnykov, P. A. (Global Science Center LP, 2023)
he structural-phase state and mechanical properties of plasma coatings sprayed with a composite material based on a self-fluxing alloy of the PG-10N-01 NiCrBSi system modified with a composite material obtained using self-propagating high-temperature synthesis were studied.
Keywords: structure; phase composition; microhardness; wear resistance